Pemberdayaan Guru sebagai Implementator Kurikulum PAI yang Efektif - Hidayah, Miftahul (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to identify and develop teacher empowerment strategies so that they can implement the Islamic Religious Education (PAI) Curriculum effectively and optimally. This research uses a qualitative method with a library approach, which is descriptive and uses inductive analysis to understand the phenomenon in depth. Data sources come from secondary literature such as books, scientific journals, papers and other writings that are relevant to the research topic. The data analysis technique used is content analysis, which involves collecting, reviewing and analyzing relevant literature. This research found that the implementation of the Islamic Religious Education (PAI) curriculum in Indonesia faces challenges such as low teacher welfare, shortage of teaching staff, lack of training, and inadequate facilities and infrastructure. To overcome this, steps are recommended such as improving teacher welfare, applicable training, improving facilities and infrastructure, and reducing administrative burdens. A holistic approach to teacher empowerment is essential, including training, professional development, and collaborative support. Support from various parties such as the school principal, colleagues, students and parents is also essential. With these strategies, it is hoped that the quality of PAI education can be improved, achieving the goal of inclusive and adaptive Islamic education.